Real-time quantification of protein expression at the single-cell level via dynamic protein synthesis translocation reporters - Delphine Aymoz; Victoria Wosika; Eric Durandau; Serge Pelet (Nature Communications, 2016)
Single cells can display large heterogeneity in gene induction. Here, Aymoz et al. present an expression reporter based on protein translocation that can accurately measure both the levels and dynamics of protein synthesis in live single cells with a temporal resolution of less than one minute.